2022
DOI: 10.1101/2022.11.01.514687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of lysergic acid diethylamide (LSD) on whole-brain functional and effective connectivity

Abstract: Psychedelics have emerged as promising candidate treatments for various psychiatric conditions, and given their clinical potential, there is a need to identify biomarkers that underlie their effects. Here, we investigate the neural mechanisms of lysergic acid diethylamide (LSD) using regression dynamic causal modelling (rDCM), a novel technique that assesses whole-brain effective connectivity (EC) during resting-state functional magnetic resonance imaging (fMRI). We modelled data from two randomized, placebo-c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…42 Additionally, a report on LSD by Bedford et al even found that changes in the angular gyrus may correlate with subjective effects of the drug. 43 For Psilocybin and Salvinorin-A, when claustral FC increased to specific clusters in the frontal cortex (Figure 1), the angular gyrus tended to have reduced FC to those same regions (Figure 2). Overlapping changes from the angular gyrus seed were characterized by reduced FC to PFC areas for psilocybin (Figure 2A) and Salvinorin-A (Figure 2B), pointing to CCC modulatory action.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…42 Additionally, a report on LSD by Bedford et al even found that changes in the angular gyrus may correlate with subjective effects of the drug. 43 For Psilocybin and Salvinorin-A, when claustral FC increased to specific clusters in the frontal cortex (Figure 1), the angular gyrus tended to have reduced FC to those same regions (Figure 2). Overlapping changes from the angular gyrus seed were characterized by reduced FC to PFC areas for psilocybin (Figure 2A) and Salvinorin-A (Figure 2B), pointing to CCC modulatory action.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Besides the well-established roles of GABA A receptors, emerging evidence has identified this very specific subunit as a promising therapeutic target for addressing a wide spectrum of neurological and neuropsychiatric disorders (65,66). Interestingly, functional magnetic resonance imaging (fMRI) studies suggest that LSD perturbs the excitation/inhibition balance of the brain (67). On the other hand, OGA is an enzyme that mediates the removal of O-GlcNAc from target proteins (68).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate which thalamic nuclei display thalamocortical hyperconnectivity, it is crucial to identify an experimental tool that can selectively elicit hallucinatory experiences without additional confounding effects. For example, while thalamocortical connectivity during psychotic states and psychedelic experiences has been extensively investigated (Anticevic et al, 2014a, 2014b; Müller et al, 2017; Ferri et al, 2018; Preller et al, 2019; Avram et al, 2020, 2022; Bedford et al, 2023; Pizzi et al, 2023), hallucinatory experiences within these populations co-occur with other physiological effects, such as long-term compensatory changes for psychotic patients (Lieslehto et al, 2021) and widespread systemic effects arising from pharmacological intervention (Schmid et al, 2015; Luppi et al, 2021; Hirschfeld et al, 2023). This means that the described neural correlates are not necessarily specific to the visual experience.…”
Section: Introductionmentioning
confidence: 99%